1996
DOI: 10.1046/j.1365-3156.1996.d01-81.x
|View full text |Cite
|
Sign up to set email alerts
|

Arginine vasopressin mediates the chloroquine induced increase in renal sodium excretion

Abstract: SummaryWe postulated that chloroquine increases plasma arginine vasopressin (AVP) concentrations thus altering renal Na' clearance. Therefore, we studied a relationship between plasma AVP concentrations and urinary Na' output in separate groups of Sprague-Dawley (SD) rats administered chloroquine (3 pg/min) for T h 20 min. We also monitored Na' excretion rates in Brattleboro AVP-deficient Di rats challenged with hypotonic saline load and administered chloroquine for I h 20 min. To establish whether chloroquine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…Chloroquine treatment either 3 h before or 6 h after CLP had a significant benefit on serum creatinine, BUN, and both cortical and OSOM histology scores. As chloroquine can have diuretic and natriuretic effects under normal conditions (3,36), it is not known whether these phenomena contribute to the protective effect of chloroquine on kidney function during sepsis; we also cannot rule out an effect of chloroquine on sepsis-associated hypotension. We used serum enzyme markers as surrogates for multiple organ damage, as well as examined splenic apoptosis and reduction of circulating bacteria as surrogates for immune paralysis to assess whether chloroquine simply decreased the overall severity of sepsis, or whether there was any selectivity toward the kidney.…”
Section: Discussionmentioning
confidence: 98%
“…Chloroquine treatment either 3 h before or 6 h after CLP had a significant benefit on serum creatinine, BUN, and both cortical and OSOM histology scores. As chloroquine can have diuretic and natriuretic effects under normal conditions (3,36), it is not known whether these phenomena contribute to the protective effect of chloroquine on kidney function during sepsis; we also cannot rule out an effect of chloroquine on sepsis-associated hypotension. We used serum enzyme markers as surrogates for multiple organ damage, as well as examined splenic apoptosis and reduction of circulating bacteria as surrogates for immune paralysis to assess whether chloroquine simply decreased the overall severity of sepsis, or whether there was any selectivity toward the kidney.…”
Section: Discussionmentioning
confidence: 98%
“…The natriuretic effect seemed to be mediated by vasopressin, via V 1 receptors (Musabayane et al, 1997), because chloroquine administration to Brattleboro, vasopressin-deficient rats had no effect on Na ϩ excretion (Musabayane et al, 1996). This chloroquine-induced natriuresis was not associated with a change in blood pressure or glomerular filtration rate (Musabayane et al, 1994) nor, surprisingly, urine flow rate, despite the concurrent increase in plasma vasopressin concentration.…”
mentioning
confidence: 86%
“…We have previously reported that acute chloroquine administration in the anesthetized rat increased renal Na ϩ excretion and plasma arginine vasopressin concentration (Musabayane et al, 1994(Musabayane et al, , 1996. The natriuretic effect seemed to be mediated by vasopressin, via V 1 receptors (Musabayane et al, 1997), because chloroquine administration to Brattleboro, vasopressin-deficient rats had no effect on Na ϩ excretion (Musabayane et al, 1996).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously suggested that chloroquine stimulates a diuresis in anesthetized, euvolemic rats by a combination of nitric oxide-induced cGMP generation and prostaglandin synthesis (Ahmed et al, 2003b). Together, these could act to inhibit the increase in medullary collecting duct cAMP generation that is expected to arise after a chloroquine-induced increase in plasma vasopressin concentration (Musabayane et al, 1996;Ahmed et al, 2003a). However, in the presence of paracetamol, a combination of higher circulating vasopressin levels (Ahmed et al, 2003b) and a predicted decreased in prostaglandin synthesis may allow sufficient cAMP generation to activate aquaporin 2 insertion and facilitate water reabsorption in the collecting duct.…”
mentioning
confidence: 99%